Verbal Violence Among Gen Z on Facebook: An Analysis of Deviations from Polite Language in Social Media Communication - Asnanurulain Halalutu; Dakia N. Djou; Asna Ntelu (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
Facebook has become the primary space for Gen Z to interact, communicate, and express themselves, but this freedom of speech often leads to verbal abuse resulting from deviations from linguistic politeness. This study describes (1) the types of verbal abuse in Gen Z communication on Facebook, and (2) the forms of linguistic politeness deviations within it. Using a descriptive qualitative approach, data in the form of Gen Z comments and posts containing verbal abuse were collected through non-participant observation and documentation. Data analysis included review, selection, identification, classification, and conclusion. The results reveal various types of verbal violence, such as slander, stigmatization, stereotyping, cursing, insulting, mocking, belittling, challenging, threatening, provoking, humiliating, discrediting, and demeaning speech that violates the principles of politeness. These often take the form of insults, threats, mockery, or negative judgments that cause psychological harm and damage self-image. Keywords: verbal violence, gen z, politeness in language, facebook